Jurnal Pengaruh Penggunaan Media Belajar Powtoon Terhadap Motivasi Belajar IPA di Kelas 5 Sekolah Dasar - Ratih (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of using powtoon learning media on the motivation to learn science in class 5 SDN Cengkareng Timur 05 Pagi. This research is a quantitative research using survey method. The population in this study were students of class 5 B totaling 35 students. The data collection technique in this study was using a questionnaire. Information obtained from respondents using this questionnaire is used to find the effect of using powtoon learning media on science learning motivation. This study uses a partial test (t test) to determine the hypothesis. The results of the hypothesis obtained based on partial testing (t test) are 3,910 (tcount) > 2,034 (ttable) with a significance of 0,000 < 0,005. These results indicate that H1 is accepted and Ho is rejected, which means that there is a positive and significant influence between the powtoon learning media on the science learning motivation of the fifth grade B SDN Cengkareng Timur 05 Pagi.